THE INFLUENCE OF ORGANIZATIONAL TRANSFORMATION ON ORGANIZATIONAL PRODUCTIVITY THROUGH THE INTERVENING ROLE OF PERFORMANCE MANAGEMENT AND HUMAN RESOURCE WELFARE - Mochammad Jefri Suryadita; Rahma Ulfa Maghfiroh (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2026)
This study investigates the indirect relationship between organizational transformation and organizational productivity, mediated by performance management and human resource well-being. Using a quantitative cross-sectional survey design with 400 employees in a large Indonesian company, data were analyzed using Structural Equation Modeling (SEM). The results indicate that transformation has no direct effect on productivity. This relationship is fully mediated through two distinct pathways: transformation positively affects performance management, which, in turn, increases productivity. Conversely, transformation has a significant negative impact on human resource well-being, while human resource well-being has a strong positive effect on productivity. These findings underscore the need for a dual-focus strategy that combines adaptive performance management with proactive mitigation of the negative impact of change on employee well-being. Human resource well-being is a crucial strategic asset that must be managed to achieve increased productivity.Penelitian ini menginvestigasi hubungan tidak langsung antara transformasi organisasi dan produktivitas organisasi, yang dimediasi oleh manajemen kinerja dan kesejahteraan SDM. Menggunakan desain survei kuantitatif cross-sectional terhadap 400 karyawan di perusahaan besar Indonesia, data dianalisis dengan Structural Equation Modeling (SEM). Hasil menunjukkan tidak ada pengaruh langsung transformasi terhadap produktivitas. Hubungan ini dimediasi penuh melalui dua jalur berbeda yaitu transformasi berpengaruh positif pada manajemen kinerja, yang kemudian meningkatkan produktivitas. Sebaliknya, transformasi berdampak negatif signifikan pada kesejahteraan SDM, sementara kesejahteraan SDM berpengaruh positif kuat pada produktivitas. Temuan ini menggarisbawahi perlunya strategi fokus ganda dengan mengimplementasikan manajemen kinerja adaptif sambil secara proaktif memitigasi dampak negatif perubahan terhadap kesejahteraan karyawan. Kesejahteraan SDM adalah aset strategis krusial yang harus dikelola untuk mencapai peningkatan produktivitas.Kata Kunci: transformasi organisasi, produktivitas, manajemen kinerja, kesejahteraan SDM